Analisis Metode Pembelajaran Seni Musik dalam Mengimplementasikan Nilai Nilai Keislaman di SMA Plus Muallimin Pesantren Persis 182 Rajapolah - Ghaida Harmoni (Jurnal Pendidikan dan Sastra Inggris, 2026)
Music learning in Islamic boarding schools is often perceived as contradictory to Islamic values. However, in practice, music can be an effective medium for developing religious character when managed with the right approach. This study aims to describe the teachers' approach to implementing Islamic values in music learning at SMA Plus Muallimin Pesantren Persis 182 Rajapolah and identify supporting and inhibiting factors. This study used a qualitative approach with descriptive methods. Data collection techniques included observation, in-depth interviews, and documentation. The research subjects were arts and culture teachers and students as supporting informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that teachers applied religious, humanistic, contextual, and habituation approaches in music learning. The implementation of Islamic values was carried out through selecting songs with Islamic nuances, clarifying intentions before learning, appreciating the meaning of lyrics, instilling musical etiquette, and fostering discipline and togetherness. The main supporting factors came from the Islamic boarding school environment and school policies, while inhibiting factors included limited facilities and Islamic music references. This study concluded that Islamic value-based music learning can develop aesthetic aspects while shaping students' religious character.